THE EFFECT OF MEDIA CD INTERACTIVE ON THE IMPROVEMENT OF ENGLISH OF EARLY CHILDHOOD AND CHILDREN’S ATTENTION AT THE CLASS IN ENGLISH LANGUAGE LESSONS IN THE MUTIARA HARAPAN OF ISLAMIC PONDOK AREN TANGERANG - Eliza Ariesta (Universitas Pelita Harapan, 2022)
This study aims to determine the effect the use of Media CD Interactive on the improvement of English vocabulary of early childhood and children's attention in the classroom in English lesson at Mutiara Harapan Islamic Kindergarten, Pondok Aren Tangerang. This research is a quantitative study using experimental research methods through classroom observation and written tests. The subjects of this study were group ‘A’ students as the experimental class by comparing the learning methods before the experiment implemented, which was the method of using Flashcard media to improve children's English vocabulary and puppet shows to increase children's attention in class.The type of statistics used in this study is to test the hypothesis of the Mean value of each dependent variable through the t-test. Through data processing that has been done, the experimental improvement of English vocabulary of children Interactive CD learning media has a better effect than the use of Flashcard and on the experiment of increasing children's attention in the class using media CD Interactive also has a better effect than the use of puppet show. This is evidenced by the Mean value of the use of media CD Interactive is greater than the use of previous learning media.Bahasa Indonesia Abstrak: Penelitian ini bertujuan untuk mengetahui pengaruh penggunaan media CD Interaktif terhadap peningkatan kosakata bahasa inggris anak usia dini dan perhatian anak di kelas pada pelajaran bahasa inggris di TK Mutiara Harapan Islamic, Pondok Aren Tangerang. Penelitian ini adalah penelitian kuantitatif yang menggunakan metode penelitian eksperimen melalui observasi kelas, tes tertulis. Subjek penelitian ini adalah siswa-siswa kelompok A sebagai kelas eksperimen dengan membandingkan metode pembelajaran sebelum dilakukan eksperimen yaitu metode penggunaan media Flashcard untuk meningkatkan kosakata bahasa inggris anak dan puppet show untuk meningkatkan perhatian anak di kelas. Jenis statistik yang digunakan dalam penelitian ini adalah menguji hipotesa nilai Mean dari masing variabel terikat melalui Uji t. Melalui olah data yang telah dilakukan, pada eksperimen peningkatan kosakata bahasa inggris anak media pembelajaran CD Interaktif berpengaruh lebih baik daripada penggunaan media pembelajaran Flashcard dan pada eksperimen peningkatan perhatian anak di kelas media CD Interaktif juga berpengaruh lebih baik daripada penggunaan media puppet show. Hal ini dibuktikan dengan nilai Mean dari penggunaan media CD Interaktif lebih besar daripada penggunaan media pembelajaran sebelumnya.